Communicative Language Teaching in The 21ST Century: A Systematic Literature Review of Trends, Challenges, and Pedagogical Innovations - Ratnawati Ratnawati; Rustamoyaadash Rustamoyaadash; Eny Satriana (International Journal Labs, 2026)
This systematic literature review (SLR) examines Communicative Language Teaching (CLT) practices in English as a Foreign Language (EFL) and English for Specific Purposes (ESP) contexts, focusing on research from 2015 to 2025. The review investigates how CLT contributes to learners’ speaking competence, motivation, and intercultural communicative competence (ICC), as well as the professional development of educators. It also addresses structural constraints in implementation and innovations in digital pedagogy. The methodology followed PRISMA 2020 guidelines, using Scopus, Web of Science, and Google Scholar to identify 68 eligible peer-reviewed articles. Studies were analyzed thematically and appraised with Critical Appraisal Skills Programme (CASP) checklists to ensure rigor and relevance. The findings reveal that CLT enhances learner fluency, confidence, and engagement when implemented through interaction-rich activities such as role-plays, group discussions, and peer feedback. Integrating psychological frameworks like self-efficacy theory and Achievement Goal Theory (AGT) demonstrates that CLT fosters higher motivation and more positive attitudes in learners. Additionally, incorporating ICC frameworks has enriched CLT in multicultural classrooms by promoting empathy, reflection, and adaptability. However, the review also identifies persistent barriers to CLT adoption, including exam-driven education systems, cultural misalignments, and limited teacher training. Emerging evidence supports the efficacy of online and blended CLT models that utilize microlearning, mobile technologies, and peer assessment strategies. Teacher beliefs, teacher identity, and collaborative professional development are shown to be critical factors in shaping CLT practices. In conclusion, this review underscores CLT’s adaptability and potential in diverse linguistic and technological environments, advocating for greater institutional support. This systematic literature review (SLR) examines Communicative Language Teaching (CLT) practices in English as a Foreign Language (EFL) and English for Specific Purposes (ESP) contexts, focusing on research from 2015 to 2025. The review investigates how CLT contributes to learners’ speaking competence, motivation, and intercultural communicative competence (ICC), as well as the professional development of educators. It also addresses structural constraints in implementation and innovations in digital pedagogy. The methodology followed PRISMA 2020 guidelines, using Scopus, Web of Science, and Google Scholar to identify 68 eligible peer-reviewed articles. Studies were analyzed thematically and appraised with Critical Appraisal Skills Programme (CASP) checklists to ensure rigor and relevance. The findings reveal that CLT enhances learner fluency, confidence, and engagement when implemented through interaction-rich activities such as role-plays, group discussions, and peer feedback. Integrating psychological frameworks like self-efficacy theory and Achievement Goal Theory (AGT) demonstrates that CLT fosters higher motivation and more positive attitudes in learners. Additionally, incorporating ICC frameworks has enriched CLT in multicultural classrooms by promoting empathy, reflection, and adaptability. However, the review also identifies persistent barriers to CLT adoption, including exam-driven education systems, cultural misalignments, and limited teacher training. Emerging evidence supports the efficacy of online and blended CLT models that utilize microlearning, mobile technologies, and peer assessment strategies. Teacher beliefs, teacher identity, and collaborative professional development are shown to be critical factors in shaping CLT practices. In conclusion, this review underscores CLT’s adaptability and potential in diverse linguistic and technological environments, advocating for greater institutional support.